A review of biodegradable plastics to biodegradable microplastics: Another ecological threat to soil environments?. (20th August 2021) - Qin, Meng; Chen, Changya; Song, Biao; Shen, Maocai; Cao, Weicheng; Yang, Hailan; Zeng, Guangming; Gong, Jilai
Abstract: Biodegradable plastics attract public attention as promising substitute for non-degradable plastics that trigger serious plastic pollution, and they are claimed to be environmentally harmless and biodegradable by microorganisms. However, not all biodegradable plastics are completely degradable under natural conditions. Some of them may be disintegrated into microplastics more rapidly than conventional plastics, emerging as another threat to soil environments. As a part of microplastics, biodegradable microplastics may pose stronger negative effects on several soil species than oil-based microplastics under some conditions. Currently, there is a fiercely increasing trend to replace nondegradable plastic commodities with biodegradable ones. Therefore, to discuss the ecological safety of biodegradable plastics is essential before promoting wide application of them during commercial use. This review provided a brief introduction on biodegradable plastics and summarized their deterioration behaviors in terrestrial environments, together with evidences on releases of additives and biodegradable microplastics. Then, potential adverse effects of biodegradable microplastics in soil ecosystems, including responses on soil properties, microbial communities, and several soil species were discussed, suggesting biodegradable microplastics as a potential threat to ecological safety of soil ecosystems. By this token, biodegradable plastics might not be a panacea to the existing "white pollution" and need further exploring. Graphical abstract: Image 1 Highlights: The incomplete biodegradation of BPs leads to more accumulation of BMPs in soil. Degradation factors of BPs in soil environments are summarized. BMPs may lead to excessive carbon input and unwanted greenhouse gas emission. BMPs pose stronger negative effects than conventional MPs under some conditions. BMPs may have stronger affinity to environmental pollutants than conventional MPs.